Capturing the multidimensionality of immigrant students' acculturation patterns in Germany - Lilla, Nanine (Frontiers in Education, 2023)
Acculturation has been shown to be relevant to immigrant students’ school adjustment and academic achievement. However, there are methodological constraints to the literature and only little is known about immigrant students’ acculturation patterns as such and their distribution across different demographic groups in Germany. Conceptualizing acculturation as a multidimensional construct, this paper aims to empirically capture acculturation patterns of immigrant students living in Germany considering affective, behavioral, and cognitive aspects of acculturation. Latent profile analysis identified six distinct profiles of acculturation evocative of strong assimilation, assimilation, integration, strong separation, separation, and marginalization. Taking the two assimilationist and separationist profiles together, assimilation was most prevalent (41% of sample), followed by separation (38% of sample), and integration and marginalization each accounted for only about 11% of the sample. Inspection of demographics showed significant differences between profiles regarding gender, generation status, and ethnic group. Findings suggest that careful consideration of the operationalization of acculturation is necessary to draw valid conclusions about its relevance to school-related outcomes for immigrant students. This study can serve as a starting point showing the use of latent profile approaches, which give an expanded perspective on immigrant students’ acculturation experiences.